Siting Schools, Choosing Students? Protecting White Habitus Through Charter School Recruitment. Issue 4 (26th August 2021) - Riel, Virginia
Abstract : While many scholars agree that charter school enrollment contributes to segregation between schools, the role of siting decisions in recruitment to non‐urban charters has been overlooked. Drawing on 14 months of fieldwork to examine student recruitment in three charter schools, this article demonstrates how personnel used intentional site selection, geographic lottery priorities, tailored programs, and other recruitment strategies that catered to local communities and created predominantly white spaces. This study builds on existing knowledge about white flight between schools but from an organizational perspective, illustrating how school personnel can work to create and sustain white habitus to recruit families. These findings also contradict ideals about school choice; while charter schools are ostensibly available to families regardless of where they live, I find that charter school personnel targeted, sited in, and tailored recruitment to the pool of prospective families they wished to attract—predominantly white areas. The article contributes to the literature by demonstrating the importance of charter school organizational practices to school segregation.